Biodegradation of 2-4-6 trichlorophenol by sequencing batch reactors (SBR) equipped with a rotating biological bed and operated in an anaerobic-aerobic condition - Ghochlavi, Nahid; Aghapour, Ali Ahmad; Khorsandi, Hassan (Frontiers in Environmental Science, 2022)
Abstract: 2-4-6 Trichlorophenol (TCP) is toxic, carcinogenic, and resistant to biodegradation. In this study, a rotating biological bed (RBB) was used to improve the efficiency of Sequencing batch reactors (SBR), and it was operated in sequential anaerobic and aerobic conditions. Biofilm growth on media of rotating biological bed was also confirmed using Scanning Electron Microscopy (SEM). In this study, the effect of 2-4-6 trichlorophenol concentration (5 to 430 mg / L), hydraulic retention time (HRT) (12 to 30 h), the number of operating cycles per day (6-12 cycles/d), the type of combination of anaerobic and aerobic processes and the presence of a rotating biological bed and its rotation were studied. SBR equipped with a rotating biological bed (SBR-RBB) with the sequential anaerobic-aerobic operation in optimal operating conditions (TCP: 430 mg / L, cycles/d: 8, and HRT: 6 h) can remove nearly 100% of TCP and more than 95% of TP and COD. The role of the presence of an RBB in removing TCP, TP, and COD was 7, 20, and 23%, respectively. The role of rotation of RBB also was 23%, 10, 21, and 62%, respectively. So, SBR-RBB, with the sequential anaerobic-aerobic operation, was able to remove higher concentrations of TCP (430 mg/L) in a shorter HRT (6h) with higher efficiency (nearly 100%) compared to previous studies. Therefore, for the first time in this study, the biological treatment of 430 mg /L of TCP is reported by a biological process.